Proclus and his Legacy - Layne, Danielle; Butorac, David D.; Layne, Danielle; Butorac, David D. (Berlin/Boston De Gruyter, 2017)
Proclus and his Legacy bridges a gap in scholarship, specifically the last great head of the Platonic Academy, Proclus, and his influence in the history of philosophy and theology. These essays offer not only a companion to Late Antique metaphysics, epistemology, theology and ethics it also explores his reception in the immediate Christian, Jewish and Muslim traditions within the mediaeval, renaissance and modern eras.
English
Keywords: Classical history / classical civilisation; Western philosophy: Ancient, to c 500; Western philosophy: Medieval & Renaissance, c 500 to c 1600; Proclus; neoplatonism; reception